Presence of Clostridium botulinum and botulinum toxin in milk and udder tissue of dairy cows with suspected botulism. (13th April 2013) - Böhnel, H.; Gessler, F.
Abstract : Clostridium botulinum is an anaerobic spore‐forming bacterium prevalent in the environment, and causes botulism in man and animals via toxins. Dairy cattle may be contaminated or infected by feed, water or other environmental factors. Milk may also carry the pathogen. Hence, milk and udder samples need to be tested. The number of clinical cases of bovine botulism in Germany has been increasing since the mid‐1990s. Besides routine samples, additional 99 milk samples from 37 farms, and 51 udder samples from 51 farms from sick animals presumably affected by botulism were tested microbiologically by the mouse bioassay. Milk from three farms (8.1 per cent) contained botulinum toxin, and from two (5.4 per cent) bacterial states of C botulinum. Ten udder samples (19.6 per cent) contained toxin, and 7 (13.7 per cent) bacterial forms, including one case where both toxin and bacteria were found. The findings are discussed. Positive milk samples containing botulinum toxin or bacteria raise concern of food safety for the human consumer. Pathological udder samples may show either infection prior to, or contamination after death.